A study on therapeutic management of allergic conjunctivitis and assessment of quality of life in patients - Anish, Diviya; Biswas, Rakhi; R. H., Shobha Rani; Komarla, Nagendra Prasad; K., Paranjyothi; Ruhana; S., Sangeetha; L., Anita (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Allergic conjunctivitis (AC) is a common ocular condition triggered by exposure to allergens. The primary objective of this study was to evaluate the therapeutic management of patients suffering from allergic conjunctivitis and to determine the prevalence of AC among patients attending an allergy center. Methods: A retro-prospective, interventional study was conducted, for a six-month period from March to August 2024. Total of 260 patients diagnosed with AC were included from total of 1,523 individuals attending the center. Inclusion criteria focused on patients of all ages undergoing treatment for AC, excluding those with infectious conjunctivitis or other ocular pathologies. Patient data were collected using structured forms that included demographic information, presenting symptoms, other allergic conditions etc. Treatments were categorized into pharmacological, personalized and supportive therapy. Results: Among all the 1,523 patients, 263 were diagnosed with AC, indicating a prevalence of 17.26%. Allergen testing revealed that dust mites were the leading triggers, followed by pollens. Coexisting allergic conditions were highly prevalent, particularly allergic rhinitis and dermatitis. Pharmacological therapy, like antihistamines and topical corticosteroids, was administered to 86 patients, while 105 patients received personalized treatments. A statistically significant improvement in post-treatment symptom scores was observed, with an effect size of 1.62, indicating high treatment efficacy. Conclusions: This study highlights the need for early diagnosis, comprehensive allergen evaluation and targeted management in allergic conjunctivitis. The study contributes to the scientific understanding of AC by providing real-world data on allergen prevalence and treatment outcomes.